2017
DOI: 10.1038/ncomms14064
|View full text |Cite
|
Sign up to set email alerts
|

Polyglucose nanoparticles with renal elimination and macrophage avidity facilitate PET imaging in ischaemic heart disease

Abstract: Tissue macrophage numbers vary during health versus disease. Abundant inflammatory macrophages destruct tissues, leading to atherosclerosis, myocardial infarction and heart failure. Emerging therapeutic options create interest in monitoring macrophages in patients. Here we describe positron emission tomography (PET) imaging with 18F-Macroflor, a modified polyglucose nanoparticle with high avidity for macrophages. Due to its small size, Macroflor is excreted renally, a prerequisite for imaging with the isotope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 31 publications
2
99
0
Order By: Relevance
“…Experimental atherosclerosis has been quantified and characterized by several modalities, including ultrasound, 202 magnetic resonance imaging, 203,204 and positron emission tomography, sometimes in combination with computed tomography. 205,206 There have also been applications to experimental atherosclerosis using multimodality imaging such as positron emission tomography/magnetic resonance imaging. 207 Although noninvasive imaging holds promise, the resolution of these modalities provides a barrier to accurately determining lesion size in experimental atherosclerosis, particularly in mice.…”
Section: Noninvasive Imagingmentioning
confidence: 99%
“…Experimental atherosclerosis has been quantified and characterized by several modalities, including ultrasound, 202 magnetic resonance imaging, 203,204 and positron emission tomography, sometimes in combination with computed tomography. 205,206 There have also been applications to experimental atherosclerosis using multimodality imaging such as positron emission tomography/magnetic resonance imaging. 207 Although noninvasive imaging holds promise, the resolution of these modalities provides a barrier to accurately determining lesion size in experimental atherosclerosis, particularly in mice.…”
Section: Noninvasive Imagingmentioning
confidence: 99%
“…Intravital microscopy displayed extravasation and cellular uptake kinetics in CX3CR1 GFP reporter mice: 30 minutes after injection, Macroflor nanoparticles cleared from the blood stream and colocalized with CX3CR1 GFP macrophages in the myocardium (Fig. 3A, B) 32 . The optical time-lapse data on uptake by macrophages revealed that these nanoparticles were ingested by macrophages within a time frame that enables 1 PET imaging with the short isotope blood half-life of 18 F (~20 min).…”
Section: Immune - Cardiovascular System Interactionsmentioning
confidence: 99%
“…(F) In vivo MRI contrast to noise ratio (CNR) in infarct 90 min after IV myeloperoxidase -Gd injection. From Keliher et al 32 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations